Characterization and Modification of Corn Starch (Zea mays [L.]) and HPMC with Sodium Tripolyphosphate as Crosslinking Agent - Muhammad Abdillah; Suprapto (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Corn starch is one type of starch that has the potential to be developed as an excipient in the manufacture of pharmaceutical preparations. However, this corn starch still has shortcomings in its flowability and compactibility. Based on this, corn starch needs to be modified physically and chemically by using the crosslinking method, namely changing the hydroxy group (OH-) with a phosphate group with sodium tripolyphosphate as the crosslink agent and HPMC as the polymer. The purpose of this study was to determine the physical and chemical characterization in the modification of corn starch-HPMC to various concentrations of sodium tripolyphosphate as a crosslinking agent. This study made 4 formulas with HPMC 10% and various concentrations of STPP (without treatment, 0.5%, 1%, and 2%). The modified starch will be characterized including FTIR test, SEM, swelling test, flow properties, and angle of repose. The results obtained in the FTIR test that the crosslink formed was at a concentration of 1% and 2% STPP which was indicated by the presence of an absorption band of the P-O-C group in the 1018cm-1 wave. The SEM test results showed that the addition of HPMC and STPP affected the physical form of starch with a rough and tight surface. In the swelling test, the modified starch increased with increasing STPP. In the flow properties test and the angle of repose, the modified starch has good flow properties and meets the requirements for a good angle of repose.